Feeding behaviour of wintering Pink-footed and Greylag Geese in north-east Scotland - Bell, M V (Wildfowl, 1988)
The feeding areas used by Pink-footed and Greylag Geese in north-east Scotland between the 1977-78 and 1985-86 winters are described together with their feeding preferences over the latter three winters. At all sites the former fed closer to the roosts than the latter, median distances being 4.0 km and 10.7 km respectively. This difference was most marked at Loch of Strathbeg where large numbers of each species occurred and where 87.5% of Pink-footed Geese fed within 8 km of the roost, whereas 84.4% of Greylag Geese fed between 8 and 18 km of the roost. Greylag tended to forage further in autumn than during the remainder of the winter. In autumn cereal stubbles were the preferred field type, with the geese progressively moving on to grass later in the winter. The proportion of geese feeding on stubbles and winter cereals was inversely related depending on the timing of the harvest, subsequent ploughing and resowing. The monthly pattern of field usages were similar in the 1983-84 and 1984-85 winters but stubble was utilised for much longer after the late and dirty harvest of autumn 1985. Waste potatoes, turnips and spring cereals were minor food sources.